Study About Urban Mobility in the Brazilian Context - Avella Netto , Nelson (2017)
Urban mobility is usually understood as something segmented and restricted to subjects related to traffic engineering and pricing policy, recently linked to environmental problems too. The goal of this article was to reach a systemic vision and understand how urban mobility relates also to social, cultural, historical, economical and healthy aspects. A methodology was used including bibliographic research, interviews with specialists and a cross-sectional analysis of these interviews, in order to analyze the context of urban mobility and present tendencies and paths for a more sustainable approach. The result was that the crisis observed nowadays, caused by the unbridled urban developmentism based on the car-based consumerist culture, and evidenced not only by the critical immobility observed on the cities but also by the protests of society, placing urban mobility on the heart of the discussions. Tendencies and sustainable paths were indicated so that urban mobility is a variable that contributes to the well-being of people, equating opportunities and wealth as well as preserving the planet’s ecosystem. The conclusion is that the scenario presents good perspectives to promote a wide discussion regarding the improvement of the quality of urban mobility, and consistent changes are possible according to the change in people´s awareness.